17α-hydroxyprogesterone and cortisol serum levels in neonates and young children: Influence of age, gestational age, gender and methodological procedures - Ballerini, Maria Gabriela (2010)
To determine the influence of age, gestational age, gender and methodological protocol on serum 170HP and Cortisol concentrations. 170HP in non-extracted (NE) and extracted (E) sera was measured by RIA in 319 full-term (FT) (1 d-5 yr) infants, 38 pre-term (PT) and in 19 neonates with classical CAH at diagnosis. 170HP (NE- and E-) decreased with age in normal children. The extraction procedure significantly reduced 170HP by eliminating interfering steroids in children <1 year. Sexual dimorphism was only observed in NE-17OHP. 170HP in PT was always higher than in FT up to 2 months of age (p <0.001). Neither NE- nor E-170HP in CAH overlapped with those of FT or PT (p<0.001) allowing to omit the extraction procedure to confirm CAH diagnosis. Cortisol levels were within normal range in neonates with CAH, thus not adding useful information about adrenal function. Chronological and gestational age, gender, and extraction for 170HP measurement are important factors to know when assessing adrenal function during the first year of life.